PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PENGGUNA MOBILE APPLICATION TIKET.COM PADA WISATAWAN DOMESTIK DI BALI - Ni Putu Evi Wijayanti (JURNAL KEPARIWISATAAN, 2020)
Service quality is one of the important factors in customer satisfaction. This study explains how much influence the quality of services provided by Tiket.com through the mobile application means. The indicators used to measure the quality of this service use the theory of E-Servqual which includes efficiency, compliance, system availability, and privacy. This indicator is used to see how much influence the quality of service on the Tiket.com mobile application has on user customer satisfaction for domestic tourists in Bali. In addition to the E-Servqual theory, this study uses the S-R (Stimulus and Response) theory. This study uses an explanatory quantitative research method with data collection techniques, namely the distribution of questionnaires to 100 respondents of domestic tourists in Bali, with an accidental sampling technique, namely choosing anyone who happens to be found as a sample. And the data analysis technique in this study used a simple linear regression analysis technique. The results of this study indicate that the contribution of the service quality variable (x) to customer satisfaction (y) is 82.4%. While the remaining 17.6% is influenced by other variables not included in this study.